2020
DOI: 10.1210/clinem/dgaa453
|View full text |Cite
|
Sign up to set email alerts
|

Development of Autoimmune Thyroid Disease in Multiple Sclerosis Patients Post-Alemtuzumab Improves Treatment Response

Abstract: Context Alemtuzumab is an anti-CD52 monoclonal antibody used in the treatment of relapsing-remitting multiple sclerosis (MS). Between 20-40% of alemtuzumab-treated MS patients develop autoimmune thyroid disease (AITD) as a side effect. Objective To determine whether MS disease progression following alemtuzumab treatment differs in patients that develop AITD compared to those who do not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Development of GD after alemtuzumab treatment was associated with reduced risk of new MS attacks and lesions on MRI, consistent with earlier findings ( 20 ). The mechanism for this remains unclear but is interesting from an immunological standpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Development of GD after alemtuzumab treatment was associated with reduced risk of new MS attacks and lesions on MRI, consistent with earlier findings ( 20 ). The mechanism for this remains unclear but is interesting from an immunological standpoint.…”
Section: Discussionsupporting
confidence: 90%
“…However, this finding was not supported by reductions in the rates of relapse or lesion formation on MRIs. In contrast, a previous study showed that both disability and disease activity were reduced in patients with AITD post-ALZ compared to patients without AITD ( 48 ). Estimating disability with EDSS at specific time points is less reliable compared to CDW due to intra- and inter-rater variability and to the short-term impact of relapses ( 12 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 62%
“…16 By contrast, Sovetkina et al reported significantly fewer relapses, longer relapse-free survival, and reduced disability progression over 2 years in alemtuzumab-treated MS patients with thyroid autoimmunity versus those without. 34 There are several important differences between Sovetkina et al and our study that could explain these disparate findings, including a much smaller sample size ( n = 33 patients with thyroid AEs versus n = 286 in our study), higher baseline EDSS score (mean 4.5 for patients with thyroid AEs versus 2.4 in our study), and higher percentage of patients treated with carbimazole (66.7% versus 8.4% in our study), a drug with considerable anti-inflammatory properties. 35 Future research should ascertain whether pre-treatment disability status or carbimazole use influences MS outcomes for alemtuzumab-treated patients.…”
Section: Discussionmentioning
confidence: 99%